KEKOSONGAN HUKUM DEEPFAKE SEBAGAI ALAT KEJAHATAN DALAM SISTEM HUKUM PIDANA INDONESIA - Benediktus Budi Darmawan Wicaksono (SAPIENTIA ET VIRTUS, 2025)
The rapid development of artificial intelligence has led to the emergence of deepfake technology, which enables the manipulation of images, audio, and video in a highly realistic manner. While this technology offers benefits in creative industries and education, it also poses significant risks when misused for criminal purposes, such as fraud, defamation, identity theft, and political disinformation. This study aims to analyze the adequacy of Indonesian positive law in regulating deepfake as a tool of crime and to identify the existing legal gaps. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that existing regulations have not explicitly addressed deepfake technology, resulting in reliance on general legal interpretations. Legal gaps are identified in the absence of clear definitions, lack of digital forensic standards, and unclear liability frameworks involving multiple actors. Therefore, legal reform is necessary to ensure legal certainty and effective protection for society against emerging digital crimes.